2003
DOI: 10.1021/nl025975r
|View full text |Cite
|
Sign up to set email alerts
|

Scanning Tunneling Microscopy/Spectroscopy Studies of Lanthanum Endohedral Metallofullerenes

Abstract: We have investigated monolayer and multilayer islands of La 2 @C 80 and La@C 82 molecules grown on a hydrogen-terminated Si(100)-2 × 1 surfaces by ultrahigh vacuum scanning tunneling microscopy. The observed La 2 @C 80 molecule has a spherical shape, consistent with a recent result by synchrotron X-ray measurements. The energy gap for the La 2 @C 80 multilayer islands is measured to be 1.3−1.5 eV, whereas that for La@C 82 is 0.5 eV, indicating that the I h cage of the La 2 @C 80 molecule is highly stabilized b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
48
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(59 citation statements)
references
References 24 publications
10
48
1
Order By: Relevance
“…Details of the preparation of the hydrogen terminated Si(100)2×1 (Si(100)2×1-H) surface are described elsewhere [3]. The La 2 @C 80 , La@C 82 and La 2 @C 72 metallofullerenes were prepared by the DC arc discharge method and were isolated with high performance liquid chromatography [3,8].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Details of the preparation of the hydrogen terminated Si(100)2×1 (Si(100)2×1-H) surface are described elsewhere [3]. The La 2 @C 80 , La@C 82 and La 2 @C 72 metallofullerenes were prepared by the DC arc discharge method and were isolated with high performance liquid chromatography [3,8].…”
Section: Methodsmentioning
confidence: 99%
“…Cage structures of the fullerenes and properties of encapsulated metal atoms of various endohedral metallofullerenes play important roles for determining the electronic properties of endohedral metallofullerenes. Scanning tunneling microscopy/spectroscopy (STM/STS) is a useful method to directly image the structures and electronic properties of fullerenes and endohedral metallofullerenes with an atomic resolution and a number of STM studies have previously been performed to characterize fullerenes on various surfaces [2][3][4][5][6][7]. In this letter, we report structures and electronic properties of La 2 @C 80 , La@C 82 and La 2 @C 72 molecules in monolayer and multi-layer islands grown on a hydrogen terminated Si(100)-2×1 surface by using an UHV-STM.…”
Section: Introductionmentioning
confidence: 99%
“…Most of them require macroscopic quantities of metallofullerenes and give either ensemble averaged or spatially averaged results. It has been a challenging task to characterize the local properties of isolated metallofullerene molecules [8][9][10][11]. Here we show that scanning tunneling microscopy (STM) can be used to detect the encapsulated metal atom inside a fullerene cage.…”
mentioning
confidence: 99%
“…It was found that the Tb@C 82 molecules were randomly distributed on the surface of Si(100) but form a close-packing monolayer on the C 60 film. However, on a hydrogen-terminated Si(100)-2 × 1 surface, Shinohara et al found in the UHV-STM images that La@C 82 molecules in the multilayer show the ordered hexagonal close-packing array although La@C 82 molecules in the monolayer show an disordered adalyer on the surface [20].…”
Section: Introductionmentioning
confidence: 99%
“…Fullerenes with metal atoms encapsulated (endohedral metallofullerenes) are novel forms of fullerene-based materials [18][19][20]. Shi et al investigated Tb@C 82 molecules adsorbed on Si(100) 2 × 1 surface and the C 60 film with an ultrahigh vacuum scanning tunneling microscope (UHV-STM) [18].…”
Section: Introductionmentioning
confidence: 99%